Effect of Akshi Tarpana & Netrashani Ras in Timira w.s.r to Simple Myopia (International Journal of Ayurveda and Pharma Research, 2025)
The eye, often described as the window to the soul, holds a central place in Ayurveda, where it is referred to as “Sarvendriyanam Nayanam Pradhanam”, signifying its status as the primary sense organ. This case report evaluates the effectiveness of Netrashani Rasa in combination with Mahatriphaladya Ghrita Akshitarpana in the management of Timira w.s.r to simple myopia. A 24-year-old male patient presented to the OPD of Dayanand Ayurvedic College, Jalandhar, with complaints of progressive diminution of distant vision in both eyes for the past 10 years. Detailed history taking and visual acuity examination confirmed the diagnosis of Timira (simple myopia). The patient was treated with oral administration of Netrashani Ras along with Mahatriphaladya Ghrita Akshitarpana. The combined therapeutic approach showed encouraging improvements in visual acuity as well as in subjective symptoms. No adverse effects were observed during or after the course of treatment. The findings suggest that the integration of internal and local ocular therapies in Ayurveda may offer a safe and effective approach in the management of simple myopia.